THE EFFECTIVENESS OF A VIRTUAL REALITY-BASED FOREHAND SMASH TRAINING MODEL IN ENHANCING TECHNICAL SKILLS OF JUNIOR TABLE TENNIS ATHLETES - Jusrianto As; Novita Wulandari; Ninik Septyani; Emayanti Anggraeni (RADJA PUBLIKA, 2025)
This study aims to develop and test the effectiveness of the Virtual Reality (VR) based forehand smash training model in improving forehand smash technique skills in table tennis athletes aged 12-16 years. In this study, the VR training model is designed to provide more immersive, flexible, and interactive training, which is expected to accelerate the learning process of forehand smash techniques without space and time limitations. This study used a research and development (R&D) approach involving 30 table tennis athletes who underwent trials of VR-based training models. The results showed that the use of VR had a significant impact on improving forehand smash skills, with an increase in scores between 15% to 30% in the pretest and posttest trials. Statistical analysis using t-test showed a significant difference between pretest and posttest scores (p-value = 0.000), indicating that VR is effective in improving speed, accuracy, and consistency of forehand smash technique. VR technology was also shown to increase athletes' motivation and engagement in training, which are important factors in technique mastery. However, although VR is effective for athletes who are still in the beginner or intermediate stages, this study also showed that highly skilled athletes experienced smaller improvements, which suggests that VR may be more effective for basic technique development. This study suggests continuing to develop VR technology by adjusting the difficulty level of the exercises according to athletes' abilities, as well as improving the comfort and user interface of VR devices. Overall, this study provides strong evidence that VR can be an effective training tool.